Synthesis and biological evaluation of conformationally restricted adenine bicycloribonucleosides1. Issue 35 (21st September 2015) - Hřebabecký, Hubert; Procházková, Eliška; Šála, Michal; Plačková, Pavla; Tloušťová, Eva; Barauskas, Ona; Lee, Yu-Jen; Tian, Yang; Mackman, Richard; Nencka, Radim
<x xml:space="preserve">Abstract</x> We prepared a novel series of conformationally restricted bicyclonucleosides and nucleotides.